‘What has the BBC ever done for us?’: ontological security and broadcasting in an online era - Taylor-Camara, Ayesha (2024)
To inform, educate, and entertain are the three guiding value principles that have shaped the BBC and its remit since its inception under Lord Reith, its founder and first Director-General. However, with a century-long existence, the BBC faces ongoing challenges to its perceived value and role within an ever-evolving media landscape characterised by technological innovation, the proliferation of online media services, and audience fragmentation. This thesis explores and redefines the value of the BBC within Britain by interrogating its ontological function within everyday life.